Experimental study and mathematical modelling of face milling forces of high-strength high-viscosity shipbuilding steel (Fracture and Structural Integrity, 2024)
Mechanical processing of hole edges in large-size hull structures of single and double curvature for welding saturation parts into them is an urgent task of shipbuilding. A considerable amount of such machining has to be performed directly on the slipway on a fully assembled structure. To perform such works non-stationary technological machining complexes are used, which have reduced rigidity in comparison with stationary equipment. The article summarizes the results of mathematical modeling of cutting forces during face milling of a workpiece made of high-strength high-viscosity shipbuilding steel. The application of high-speed face milling in order to reduce the value and non-uniformity of cutting forces is theoretically substantiated. Recommendations for selection of technological cutting modes and tool geometry are determined. The obtained experimental data confirm the possibility and expediency of high-speed face milling of hull structures made of hard-to-machine materials under conditions of a low-rigid technological system.
Keywords: Non-stationary technological processing complex; face milling; bevel faces; ship hull structure; high-strength high-viscosity shipbuilding steel